FAMILY TO WORK CONFLICT AMONG WORKING MOTHERS IN UAE - Nasreen Khan (European Scientific Journal, ESJ, 2014)
With an increasing participation of female employees in the workforce, there has been a surge in research studies that would be examining the interface and interdependence of work and family. The researcher has analyzed the family to work conflict experienced by working mothers in UAE’s educational sector. This research work will be essentially helpful in understanding the spillover of family domain onto work related outcomes. Data was collected from female employees married with children. As working mothers have various roles to perform at home and at the same time they have to fulfill their role responsibilities at work, they were found to be experiencing conflicting demands from both the domains. The findings of this research study show that family to work conflict plays a significant role, thus causing negative impact on work related outcomes.